Financial Inclusion in Asia-Pacific - Loukoianova, Elena (Departmental Papers; Departmental Paper, 2018)
Asia has made significant progress in financial inclusion, but both its across-country and intra-country disparities are among the highest in the world. The gaps between the rich and the poor, rural and urban populations, and men and women remain deep. Income is the main determinant of the level of financial inclusion; but other factors, such as geography, financial sector structure, and policies, also play important roles. While some countries in the Asia-Pacific region are leaders in fintech, on average the region lags behind others in several important areas such as online (internet) purchases, electronic payments, mobile money, and mobile government transfers. This Departmental Paper aims to take stock of the development and current state of financial inclusion and shed light on policies to advance financial inclusion in the region. The research focuses on the impact of financial inclusion on economic growth, poverty reduction, and inequality, linkages between financial inclusion and macroeconomic policies, as well as structural policies that are important for improving financial inclusion. Given the increasing importance of financial technologies (fintech), the paper also provides a snapshot of the fintech landscape in the Asia-Pacific.